The Secret Garden - Burnett, Frances Hodgson, 1849-1924.; Brodey, Kenneth; Manna, Giovanni, 1966-; Pereira, Jenny (Genoa [Italy] : Black Cat, 2007)
A retelling of Frances Hodgson Burnett's "The Secret Garden," that includes activities, questions and answers, and audio CD.
"Step two, B1.1"--Cover.
Enhanced compact disc.
3-6
Young Adult.
Keywords: Readers (Elementary).; Audiobooks, English (Elementary).; Audiobooks -- English fiction; Reading training, English (Elementary).